Do green investments react to oil price shocks? Implications for sustainable development - Dutta, Anupam; Jana, R. K.; Das, Debojyoti (Elsevier, 2020)
This study investigates whether green investments are connected to oil price shocks. While earlier papers mainly investigate the linkage between clean energy stock and crude oil prices, we consider recently introduced environmental indexes consisting of companies that use eco-friendly production processes and develop green infrastructures. Using the Markov regime switching regression approach, we observe that the effect of crude oil prices on environmental investments appears to be statistically insignificant, albeit positive in most of the cases. One possible reason behind such a finding is that the oil-dependence is limited to the case of eco-friendly firms. The results further indicate switching between low and high volatility regimes implying that there exist high and low volatility states for green assets. Given that growing concerns about climate change and energy security would inspire market participants shift towards ethical investments, our results could be of interest to investors aiming at decarbonizing their portfolios by including more environmental assets. One important finding of our empirical analysis is that green assets are found to be more susceptible to oil market volatility rather than to oil price fluctuations. This is a novel finding given that prior literature focusing on the association of oil sectors and green assets mainly consider the information on oil prices rather than oil volatility. Hence, our study aims to conceal an important void in the exiting literature.
Keywords: green investments; environmental assets; oil price shocks; regime shifts; sustainable development; prices; oil; volatility (societal properties); energy; security market; econometrics; pricing; crude oil; renewable energy sources; ecoenergy; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|